Organophosphorus flame retardants and their metabolites in paired human blood and urine - Yantao Guo; Mengqin Chen; Mengxi Liao; Shijun Su; Weiyi Sun; Zhiwei Gan (Ecotoxicology and Environmental Safety, 2023)
Organophosphorus flame retardants (OPFRs) have been shown to be carcinogenic, neurotoxic, and endocrine disruptive, so it is important to understand the levels of OPFRs in human body as well as the modes of external exposure. In this study, we investigated the levels of 13 OPFRs and 7 phosphodiester metabolites in paired human blood and urine, as well as the influencing factors (region, age and gender), and studied the relationship between OPFRs and oxidative stress by urinary metabolites. We found that the concentrations of triphenyl phosphate (TPhP) and tris-(2-ethylhexyl) phosphate (TEHP) in the blood of urban populations were higher than those of rural populations, and that younger populations suffered higher TPhP and 2-ethylhexyl diphenyl phosphate (EHDPP) exposures than older populations. In addition, we found that tris-(2-chloroethyl) phosphate (TCEP), tributyl phosphate (TnBP), TPhP and EHDPP exposure induced oxidative stress. The results of the internal load principal component analysis indicated that dust ingestion, skin exposure, respiration and dietary intake may be the most important sources of TCEP, tris(2-butoxyethyl) phosphate (TBOEP), tri(2-chloroisopropyl) phosphate (TCIPP) and TEHP, respectively, and dust ingestion and skin exposure may be the main sources of TPhP for humans.